A Review on Carbon Emissions in Malaysian Cement Industry - Bakhtyar, B.; Kacemi, Tarek; Nawaz, Md Atif (International Journal of Energy Economics and Policy, 2017)
Cement production is an energy and carbon-intensive process. Hence, they are a noteworthy contributor to global anthropogenic CO2 emissions. The cement industry has always been among the greatest CO2 discharge sources with 900 kg CO2 released with each production ton of cement. Malaysia massive amount of biogenic wastes, palms oil fuel ash, rice husk ash, sawdust ash/ash from timber. Around 0.3 million ton of palm oil fuel ash is produced every year in Malaysia, yet there are no noteworthy employments uses of these ashes. Disregarding Malaysia technical and financial benefits, till date these ashes, are only used for landfill purposes. Excessively dependent on this energy will lead to an expansion in CO2 emission that consequently responsible for the global warming. Researchers discover by substituting fossil fuels with alternative fuels will lead to lessening in carbon dioxide emissions. Hence, we suggest that by eliminating legal, economic obstructions, CO2 mitigation strategies can be applied on the extensive scale of the cement industry to a globally acceptable emission targets in each nation. Furthermore, the relatively small number of participants signifies that an agreement for the cement market in Malaysia can probably be reached easily between the parties in decreasing CO2 emissions. Keywords: Carbon Emission, Cement Industry, Energy Consumption JEL Classifications: Q01, Q53, Q54